Health measurement scales a practical guide to their development and use - Streiner, David L.; Norman, Geoffrey R. (Oxford : Oxford University Press, 2008)
This title offers a practical guide for clinicians developing tools to measure subjective states, attitudes or non-tangible outcomes in their patients. It provides details on cognitive requirements in answering questions, and outlines how these might influence scale development.
Previous ed.: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health status indicators -- Measurement; Health surveys; Public health -- Evaluation; Medical care -- Evaluation